Effects of a 2‐year exercise training on neuromuscular system health in older individuals with low muscle function. Issue 2 (28th January 2023) - Monti, Elena; Tagliaferri, Sara; Zampieri, Sandra; Sarto, Fabio; Sirago, Giuseppe; Franchi, Martino Vladimiro; Ticinesi, Andrea; Longobucco, Yari; Adorni, Elisa; Lauretani, Fulvio; Von Haehling, Stephan; Marzetti, Emanuele; et al.
Abstract: Background: Ageing is accompanied by a progressive loss of skeletal muscle mass and strength, potentially determining the insurgence of sarcopenia. Evidence suggests that motoneuron and neuromuscular junction (NMJ) degeneration contribute to sarcopenia pathogenesis. Seeking for strategies able to slow down sarcopenia insurgence and progression, we investigated whether a 2‐year mixed‐model training involving aerobic, strength and balance exercises would be effective for improving or preserving motoneuronal health and NMJ stability, together with muscle mass, strength and functionality in an old, sarcopenic population. Methods: Forty‐five sarcopenic elderly (34 females; 11 males) with low dual‐energy X‐ray absorptiometry (DXA) lean mass and Short Physical Performance Battery (SPPB) score <9 were randomly assigned to either a control group [Healthy Aging Lifestyle Education (HALE), n = 21] or an intervention group [MultiComponent Intervention (MCI), n = 24]. MCI trained three times per week for 2 years with a mix of aerobic, strength and balance exercises matched with nutritional advice. Before and after the intervention, ultrasound scans of the vastus lateralis (VL), SPPB and a blood sample were obtained. VL architecture [pennation angle (PA) and fascicle length (Lf)] and cross‐sectional area (CSA) were measured. As biomarkers of neuronal health and NMJ stability status, neurofilament light chain (NfL) and C‐terminal agrin fragment (CAF) concentrations were measured in serum. Differences in ultrasound parameters, NfL and CAF concentration and physical performance between baseline and follow‐up were tested with mixed ANOVA or Wilcoxon test. The relationship between changes in physical performance and NfL or CAF concentration was assessed through correlation analyses. Results: At follow‐up, MCI showed preserved VL architecture (PA, Lf) despite a reduced CSA (−8.4%, P < 0.001), accompanied by maintained CAF concentration and ameliorated overall SPPB performance ( P = 0.007). Conversely, HALE showed 12.7% decrease in muscle CSA ( P < 0.001), together with 5.1% and 5.5% reduction in PA and Lf ( P < 0.001 and P = 0.001, respectively), and a 6.2% increase in CAF ( P = 0.009) but improved SPPB balance score ( P = 0.007). NfL concentration did not change in either group. In the population, negative correlations between changes in CAF concentration and SPPB total score were found ( P = 0.047), whereas no correlation between NfL and SPPB variations was observed. Conclusions: The present findings suggest that our 2‐year mixed aerobic, strength and balance training seemed effective for preventing the age and sarcopenia‐related increases in CAF concentration, preserving NMJ stability as well as muscle structure (PA and Lf) and improving physical performance in sarcopenic older individuals.